Multiannual phytoplankton trends in relation to environmental changes across aquatic domains: A case study from Sardinia (Mediterranean Sea). (3rd July 2016) - Pulina, S.; Suikkanen, S.; Satta, C. T.; Mariani, M. A.; Padedda, B. M.; Virdis, T.; Caddeo, T.; Sechi, N.; Lugliè, A.
Abstract : We investigated multiannual trends in phytoplankton in relation to several environmental drivers. We analyzed ecological data collected during the past two decades from three aquatic sites: an artificial lake, a coastal lagoon, and a marine coastal area. Hydrographic, nutrient, and phytoplankton data were statistically analyzed to detect trends and interactions. In all ecosystems, the chlorophyll a concentration decreased with increasing abundance of small-sized phytoplankton. Phytoplankton dynamics were related to decreased nutrient concentrations in the lake, to dynamics of phosphorus and decreased salinity in the lagoon, and probably to combined top-down and bottom-up processes in the marine gulf.